The application of microcapsules of PCM in flame resistant non-woven materials - Gomes, Jaime Rocha (2009)
The use of organic microcapsules of phase change materials (mPCM) has been gaining ground in technical textiles for temperature regulation and hence a means of keeping the body at a comfortable temperature when wearing impermeable protective clothes. However, for such applications as fire-fighter’s protective clothes, the standards require that all the material composing the material be fire resistant, including the lining made of aramid fibres. Organic PCM such as n-octadecane are the most used in textiles, since they are easily microencapsulated in Melamine-formaldehyde (MF) polymers. Paraffins such as n-octadecane however, are flammable and ignite easily. Even though they are microencapsulated, the microcapsules are porous and at high temperatures the paraffin will vaporize and diffuse through the pores. As the application of mPCM is usually through the use of binder applied on the fibres by padding or coating and binders are thermoplastic and inevitably flammable such applications increase the flammability of the material. Based on a new approach where MF microcapsules of n-octadecane were treated with different flame retardant products, either co-polymerised on the surface or attached by ion-exchange, as was the case with Zinc and Boron, it was possible to make flame-retardant microcapsules of n-octadecane. For application on the aramid non-woven, flame retardant and MF resin were applied instead of binder and the material containing the flame retardant microcapsules was then also resistant for example to the standard flame propagation test EN532.